Analisis Netralitas Uang di Indonesia Tahun 1995.1 – 2017.2 - I'zzatus Salaamah; Firmansyah Firmansyah (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2020)
This study aimed to analyze the effect of currency money, demand deposit money, and quasy money to price level and real output in Indonesia. This study uses time series data period 1995.1 – 2017.2. The analysis tools using Error Correction Model (ECM). The result of study showing there are any significant effect of changes currency money, and demand deposit money to price level and real output. On the other hand, changes in quasy money doesn’t have significant effect on real output. Separately, this showing if currency money and demand deposit are not neutral for real output and quasy money are neutral for real output. But, in general it can be concluded that neutrality of money is not applicable in Indonesia during the study period.